Price behavior and insider trading around seasoned equity offerings: the case of majority-owned firms - Hauser, Shmuel; Kraizberg, Elli; Dahan, Ruth (Journal of Corporate Finance, 2003)
Small public firms in the US and elsewhere are often managed by majority owners. This paper offers the hypothesis that majority insiders have an incentive to engage in insider trading around seasoned equity offerings (SEOs), primarily for the sake of preserving control. This hypothesis is tested side-by-side with traditional hypotheses regarding insider trading, such as signaling or growth opportunities that are often considered in the context of firms with dispersed ownership. The empirical analysis in this paper utilizes data of 76 SEOs announced by firms listed on the Tel Aviv Stock Exchange (TASE) between June 1989 and December 1997, whose inside ownership exceeds 50%. The results demonstrate the strong effect of expected post-announcement share price changes on insider trading, and a weaker effect of pre-announcement insider trading on price changes. Unlike minority insiders, who may have an incentive to trade on inside information in order to extract short-term capital gains, majority insiders appear to take the long-term view by buying shares before the offering in order to preserve or increase their control over the firm. This activity does not seem to be dependent upon the firm's growth opportunities. Rather, it seems to be market-dependent; that is, the ownership ratio of majority insiders is increased in a bear market and remains the same in a bull market.